AML system’s affect on the effectiveness and efficiency of AML controls : A case study of Bank X in the Nordic countries - Mäkelä, Joonas (My University, 2021)
During the past few decades, the European Union has continuously reinforced its anti-money laundering (AML) regulations. The increasing regulatory pressure has driven financial institutions to reform their AML controls and as a result, AML systems are implemented at an increasing rate. AML systems allow financial institutions to automate AML related processes for the purpose of making regulatory compliance easier. However, financial institutions have often failed to implement effective or efficient AML systems. Even though technology has a key role in AML controls, the research on AML systems is quite limited and often decontextualized from organizational settings. As many financial institutions are experiencing difficulties and achieving unsatisfactory results with their AML systems, the need for further research exploring AML systems’ performance in organizational settings is clear. The purpose of this thesis is to shed light on how AML systems affect the overall effectiveness and efficiency of AML controls in the case organization. This thesis is a qualitative case study and semi-structured interview was selected as an empirical data collection method. The case organization of this study, Bank X, is one of the largest Nordics banks. Four of the case organization’s employees with different roles and responsibilities within AML were selected to be the informants in this research. The case organization implemented a new AML system during the research project, which enabled the evaluation and comparison of two different AML systems. Each of the informants were interviewed twice, before and after the implementation of the new AML system. This study identified four key elements of AML systems that affected the effectiveness and efficiency of AML controls in the case organization. These elements were data quality, analytic capabilities, information management and quality, and reporting. The challenges with the old AML system were mostly due to limitations in its analytical capabilities and information management, whereas the new AML system’s affect was undermined by insufficient data quality, suboptimal configuration of scenarios, and the still unimplemented advanced technologies.

Kuluneen muutaman vuosikymmenen aikana Euroopan Unioni on jatkuvasti vahvistanut rahanpesun estämisen (AML) säännöstelyä. Lainsäädännöllisen paineen kasvu on ajanut finanssilaitokset uudistamaan AML kontrollejaan sillä seurauksella, että AML-järjestelmiä implementoidaan kiihtyvällä tahdilla. AML-järjestelmät mahdollistavat finanssilaitosten AML prosessien automatisoinnin lainsäädännöllisten vaatimusten noudattamisen helpottamiseksi. Finanssilaitokset ovat kuitenkin usein epäonnistuneet efektiivisten ja kustannustehokkaiden AML-järjestelmien implementoinnissa. AML-järjestelmiin keskittyvä tutkimus on melko suppeaa ja usein irrotettu organisatorisesta kontekstista, vaikka teknologialla on keskeinen rooli AML kontrolleissa. Tarve AML-järjestelmien suorituskyvyn tutkimiseen organisatorisessa kontekstissa on selkeä, sillä useat finanssilaitokset kokevat AML-järjestelmissään haasteita sekä saavuttavat niillä heikkolaatuisia tuloksia. Tämän tutkielman tarkoitus on tarkastella sitä, miten AML-järjestelmät vaikuttavat kohdeorganisaation AML kontrollien efektiivisyyteen ja kustannustehokkuuteen. Tämä tutkielma on kvalitatiivinen tapaustutkimus, jonka empiirisen aineiston keruumenetelmäksi valittiin puolistrukturoidut haastattelut. Tämän tutkielman kohdeorganisaatio on Pankki X, joka on yksi suurimmista Pohjoismaisista pankeista. Tutkielman vastaajiksi valikoitui neljä erilaisissa rahanpesun estämisen rooleissa ja vastuualueilla toimivaa kohdeorganisaation työntekijää. Tutkielmaprosessin aikana kohdeorganisaatio implementoi uuden AML-järjestelmän, mikä mahdollisti kahden erillisen AML-järjestelmän arvioinnin ja vertailun. Kukin vastaajista haastateltiin kahteen otteeseen, ennen ja jälkeen uuden AML-järjestelmän implementoinnin. Tutkielmassa tunnistettiin neljä tekijää, jotka olivat avainroolissa AML-järjestelmien vaikutuksessa kohdeorganisaation AML kontrollien efektiivisyyteen ja kustannustehokuuteen. Nämä tekijät olivat datan laatu, analyyttiset kyvykkyydet, informaation hallinta ja laatu, sekä raportointi. Vanhan AML-järjestelmän haasteet johtuivat pääosin sen analyyttisten ominaisuuksien ja informaation hallinnan rajoitteista. Uuden AML-järjestelmän vaikutusta heikensi riittämätön datan laatu, epäoptimaalinen skenaarioiden konfigurointi ja edistyneempien teknologioiden implementoimattomuus.
Keywords: Anti-money laundering, AML system, Analytics, Data management, System development